STUDY OF THE EFFECT OF SCIG BASED VARIABLE SPEED WIND POWER PLANT ON DISTRIBUTION SYSTEM VOLTAGE AND POWER LOSSES - Agni, Muhammad Wisnu Satriyo; Gianto, Rudy; Junaidi, Junaidi (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
Wind power plants are a type of power plant that uses wind energy as the main source to produce electrical energy. This research analyzes the effect of wind power generation on voltage and power losses under light load, peak load, and average load conditions in the distribution system. The data that will be used is 33 bus distribution system data and distribution system network data. Then thoroughly calculate the voltage and power losses of the distribution system using MATLAB software version R2016A. This research obtained the results that the lowest voltage in the 33 bus distribution system occurred on bus 18, so that bus would be connected to the PLTB. As the mechanical power of the turbine increases, the system voltage profile for various load conditions improves. In the distribution system, before the PLTB was connected, the best voltage profile at light load was 0.9378 pu and the worst voltage profile at peak load was 0.8671 pu. After the system is connected to the PLTB, the light load becomes 0.9466 pu, the peak load becomes 0.8771 pu, and the average load becomes 0.9131 pu. By connecting the system with PLTB, power losses at light loads are reduced to 184.8918 kW (Pm = 2.0200 pu), peak loads are reduced to 807.7297 kW (Pm = 3.6880 pu), and average loads - the average decreases to 437.8619 kW (Pm = 2.7709 pu).